Strontium isotope stratigraphy of late Cenozoic fossiliferous marine deposits in North Borneo (Brunei, and Sarawak, Malaysia). (15th June 2022) - Kocsis, László; Briguglio, Antonino; Cipriani, Anna; Frijia, Gianluca; Vennemann, Torsten; Baumgartner, Claudia; Roslim, Amajida
Graphical abstract: Highlights: Sr-isotope stratigraphy of fossiliferous marine deposits in northern Borneo. Burdigalian to Tortanian ages revealed for thirteen fossil-rich shallow marine deposits. Origin of reworked specimens could be traced by the obtained SIS ages. Trace element and stable isotope chemistry of the well-preserved shells can be linked to habitat-conditions. Altered and recrystallized specimens helped tracing diagenetic pathways. Abstract: Neogene marine deposits of North Borneo are locally very rich in fossils that provide glimpses into the past biodiversity. However, dating these onshore sediments with biostratigraphy is often hampered by the lack and/or the poor preservation state of index fossils. Therefore, the fossiliferous sites were targeted with strontium isotope stratigraphy (SIS) to obtain higher precision relative dating. Well-preserved macrofossils were screened using a multidisciplinary approach, and 87 Sr/ 86 Sr ratios of the most pristine remains were used to date the embedding sediments. Most of the measured ages fall in the expected chronostratigraphic framework established by large scale studies for the region. The oldest, Burdigalian (early Miocene) ages were measured for the Sibuti Formation in Sarawak (17.71 ± 0.2My and 16.7 ± 0.2My) followed by a Serravallian (middle Miocene) age within the Belait Fm in Brunei (12.1 + 1.4/-1.2My). Eight localities from the younger units, the Miri and Seria formations in Brunei, gave a range in age from 10.5 ± 1 to 7.0 + 0.9/-0.5My (Tortonian-Messinian). Reworked fossil assemblages from Tutong beach were also investigated and the SIS ages of Late Miocene support an origin from the younger part of the Seria Fm. One locality, in Lumapas where limestone crops out in Brunei, gave an unexpected younger age (Tortonian, late Miocene, 10.6 ± 1My) compared to estimates projected for its assumed stratigraphic position in the lower Belait Formation (late Burdigalian). These challenging data require more research, yet if the young age is accepted, the stratigraphic situation of the limestone needs further revision.